Curriculum Management Practices in Pedagogical Coordinations of Araucania Schools: Unveiling Technical/Instrumental Rationality, Control and Power Mechanisms Underlying - Beltrán-Véliz, Juan Carlos (2016)
This article consists of a case study regarding curriculum management practices of pedagogical coordinators in schools in Araucania area. The study aims to reveal technical/instrumental rationality, control and power mechanisms that underlie the curriculum management practices of such pedagogical coordinators of schools in Araucania region. A descriptive qualitative design based on the constructionist grounded theory and the constant comparative method is considered. Subjects studied included 12 technical leaders and 22 teachers from Araucania schools. Techniques for collecting information were semi-structured interview and texts for reading. Four categories rose from axial coding. Findings reveal that the teaching process is reduced to an instructional process. Furthermore, there is no uniformity of criteria regarding general functions that must be met. In the same extent, activity coordination is centered on bureaucratic administrative aspects, with main focus on task control. Regulations, programs and educational projects are used as control mechanisms. In addition, absence of spaces for professional discussion of pedagogical work and for constructive criticism is envisioned. This study concludes that pedagogical coordination practices are geared from an “instrumental rationality”, anchored in technical management set up in control and power.